Pharmacological characterisation of the fatty acid receptors GPR120 and FFA1 - Watson, Sarah-Jane (2013)
In recent years, two G protein coupled receptors have been de-orphanised which respond to long chain free fatty acids (FFAs), and so are able to mediate the signalling of these important nutrient molecules. FFA1 (GPR40) is predominantly expressed in pancreatic -cells, while the expression profile of GPR120 includes gut endocrine cells and adipose tissue. These distributions, together with the potential of both receptors to stimulate insulin and incretin hormone secretion, singled them out as potential drug targets for type 2 diabetes and obesity. The aim of this thesis was to evaluate the pharmacology of these receptors and their signalling properties, including the development of fluorescent FFA receptor ligands to evaluate agonist binding using imaging techniques. GPR120 has been identified to exist as two splice isoforms in humans, differing by a short insertion in the third intracellular loop, but no full isoform specific characterisation of receptor signalling and trafficking had been undertaken. This work therefore studied the GPR120S and GPR120L isoforms in terms of both G protein dependent and arrestin dependent signalling, and trafficking. It was found that the long GPR120L isoform exhibited reduced G protein signalling, but similar arrestin recruitment and lysosomal intracellular trafficking profiles as GPR120S. Potentially, expression of the long GPR120 isoform provides a mechanism to direct signalling to the arrestin pathway, for example to produce anti-inflammatory effects in macrophages. As the expression profile of GPR120 overlaps with that of FFA1, for example in colonic endocrine cells, a series of constrained GPR120 homo-dimers and GPR120:FFA1 heterodimers were created using irreversible bimolecular fluorescence complementation, and the potential for novel pharmacology was investigated by monitoring dimer internalisation. However, there was no evidence that such dimerisation altered the pharmacology of the ligand tested. Second, a model of the GPR120S ligand binding site was tested using point mutagenesis of the receptor. This mutagenesis validated key features of the model, including the role of Arg99 in co-ordinating the agonist carboxylate group, and interactions of the agonists with the conserved transmembrane VI Trp “toggle-switch” involved in receptor activation. Another mutation (Asn215) provided evidence for ligand-specific binding modes within the pocket. This study showed the complexity of testing mutants designed to interfere with ligand binding indirectly through signalling assays and highlighted the requirement for a FFA receptor binding assay to measure ligand affinity directly. In the absence of radioligands of suitable selectivity and affinity, a novel fluorescent ligand, based on the FFA1/GPR120 agonist GW9508, was used to successfully develop a whole cell FFA1 competition binding assay for the first time, obtaining FFA1 affinity estimates for a range of synthetic ligands. Fluorescent ligand binding was further investigated using fluorescence correlation spectroscopy and photon counting histogram analysis, defining the diffusion characteristics of FFA1 receptors in the membrane of single living cells, and providing preliminary evidence for their dimerisation.